Anthropometric craniofacial pattern profiles in microcephaly - Abdel-Salam, Ghada M.H.; Gyenis, Gyula; Czeizel, Andrew E. (Polskie Towarzystwo Antropologiczne, 2002)
Craniofacial measurements were taken in 60 cases prsenting with microcephaly. The cases were classified etiologically and morphologically and the letter was further subclassified. Craniofacial pattern profiles, cranial capasity, and the pattern vriability index were calculated and compared with normal Hungarian controls of the same age and sex. In addition, correlation analysis between cranial capacity and IQ was done. Our results show significant similarity of the craniofacial pattern profiles between isolated microcephaly (IMC) and multiple microcephaly (MMC), and between primary microcephaly (PMC) and secondary microcephaly (SMC). The pattern variability index of the microcephalic caseswas 4.77. There was no correlation between cranial capacity and IQ in the icrocephalic patients.
Keywords: microcephaly; cranial capacity; IQ